Upaya Peningkatan Kesehatan Jiwa melalui Terapi Aktivitas Kelompok Tie-Dye dalam Menurunkan Halusinasi Pendengaran - Feby Margareta; Wita Oktaviana; Hendri Santoso; Slamet Wibowo (LOSARI DIGITAL, 2026)
Mental disorders, particularly schizophrenia with auditory hallucination symptoms, remain a significant health problem. Most patients with schizophrenia experience hallucinations that can interfere with social functioning and daily activities. This problem is caused by patients’ inability to control hallucinatory stimuli and the lack of productive activities. Tie-dye Group Activity Therapy was conducted to reduce the frequency of auditory hallucinations and improve patients’ ability to control hallucinatory stimuli. This activity used a one-group pretest–posttest design involving five schizophrenia patients with auditory hallucinations. The evaluation results using the Auditory Hallucination Rating Scale (AHRS) showed that all respondents experienced a decrease in hallucination scores ranging from 7–11 points. Before the intervention, respondents were in the moderate to severe categories, which decreased to moderate and mild categories after the intervention. No increase in scores was found among respondents, indicating a consistent direction of improvement. Tie-dye Group Activity Therapy had a positive effect in reducing auditory hallucinations, improving social interaction, and encouraging patients’ productive activities.